Further studies of isolated photon production with a jet in deep inelastic scattering at HERA - Abramowicz, Halina; Lisovyi, Mykhailo (Journal of high energy physics, 2018)
Isolated photons with high transverse energy have been studied in deep inelastic ep scattering with the ZEUS detector at HERA, using an integrated luminosity of 326 pb−1 in the range of exchanged-photon virtuality 10-350 GeV2. Outgoing isolated photons with transverse energy 4 < E T γ < 15 GeV and pseudorapidity − 0.7 < η γ < 0.9 were measured with accompanying jets having transverse energy and pseudorapidity 2.5 < E T jet < 35 GeV and −1.5 < ηjet < 1.8, respectively. Differential cross sections are presented for the following variables: the fraction of the incoming photon energy and momentum that is transferred to the outgoing photon and the leading jet; the fraction of the incoming proton energy transferred to the photon and leading jet; the differences in azimuthal angle and pseudorapidity between the outgoing photon and the leading jet and between the outgoing photon and the scattered electron. Comparisons are made with theoretical predictions: a leading-logarithm Monte Carlo simulation, a next-to-leading-order QCD prediction, and a prediction using the k T -factorisation approach.
The ZEUS collaboration: H. Abramowicz, M. Lisovyi [und 111 weitere ]
Gesehen am 03.04.2019